2022
DOI: 10.19044/esj.2022.v18n15p106
|View full text |Cite
|
Sign up to set email alerts
|

Profit Persistence: is There A Conglomerate Effect? The Case of Banking and Insurance in Morocco

Abstract: This paper analyses profit persistence and its determinants in Morocco's banking and insurance sectors. The solid and increasing interdependencies between both actors are becoming a matter of concern for the regulatory authorities, as they threaten the country's financial stability. Using both static and dynamic hypotheses of the competitive environment model, we study the determinants of profit persistence in eight banks and eight insurance companies for 13 years, using a random-effects panel data model. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…This effect is consistent with previous research concluding that size harms bank profitability (Lemonakis et al. , 2015; Adel and Meknassi, 2022). Others observed that an increase in size led to diseconomies of scale, higher agency costs, and cumbersome operational processes (Sanderson et al.…”
Section: Resultssupporting
confidence: 93%
“…This effect is consistent with previous research concluding that size harms bank profitability (Lemonakis et al. , 2015; Adel and Meknassi, 2022). Others observed that an increase in size led to diseconomies of scale, higher agency costs, and cumbersome operational processes (Sanderson et al.…”
Section: Resultssupporting
confidence: 93%